Analisis Strategi Pemasaran Layanan Pos Express Pada PT. Pos Indonesia (Persero) Sipirok - Zernita Sari Ritonga; Ahmad Perdana Indra (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This news aimsto analyze the marketing strategy of express postal service at PT. Pos Indonesia (Persero) Sipirok. Research was conducted using qualitative research methods. The research subjects were the sipirok branch post office and sipirok community in the sub-district. While the object of the research is marketing strategy, it shows that there are problems faced by Pos Iindonesia (Persero) Sipirok regarding marketing strategy as evidenced by the results interviews with several business people and people who use express products and the many expedition companies that offer affordable and fact prices in the sipirok sub-district area. So the solution offered in determining the marketing strategy is to approach consumers by determining the target consumer based on the consumer’s desires. Meanwhile, the marketing mix used by PT. Pos Indonesia (Persero) Indonesia , branch office is the 4P marketing mix , namely product price, place, and promotion .